Subsaharianos in Spain - Cebrián, Juan A.; Bihina, Simón (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The immigration of subsaharians to Spain is explained in this article together with its causes and effects on the place of origin —subsaharian Africa— and on the place of destination —Western Europe—. Its is argued that african poverty is the main factor of emigration, much more important than political instability. In order to assess the numerical importance of the flows of african immigrants, we have used because of their accessibility, the statistics of the Interior and those provided by the african Embassies in Madrid. Both sources of data need to be purged, a task which has not been undertaken for this occasion. The most common incidents in the journey of our immigrants from Africa to Europe are then presented, based for the most part on several open surveys which have been done. Finally, the more structural repercussions of migrations from Africa to Europe and the evolution of spanish migration policy in the last few years are analysed.